IMPROVING SOCIO-EMOTIONAL ABILITIES THROUGH PROJECT BASED LEARNING AT RA BUNAYYA IV - Lita Anggraini; Salma Rozana (Yayasan Multidimensi Kreatif, 2025)
This research aims to improve children's social-emotional abilities through the application of the Project Based Learning (PjBL) learning model at RA Bunayya IV. Social-emotional skills include aspects of cooperation, interaction and following rules and instructions, which are important foundations for early childhood development. The research method used is Classroom Action Research (PTK) with 2 cycles consisting of 2 meetings in 1 cycle, so that there are 4 meetings overall. The subjects of the study were 16 children of group A RA Bunayya IV. Data is collected through observations, anecdotal notes, or assessment tables, and documentation of activities. The results of the study show that the application of Project Based Learning (PjBL) can significantly improve children's social-emotional skills. The percentage of achievement of children's social-emotional skills increased to 94% in cycle II.